2020
DOI: 10.1002/ptr.6683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of curcumin on glycemic profile, inflammatory markers, and oxidative stress in HIV‐infected individuals: A randomized controlled trial

Abstract: To evaluate the influence of curcumin supplementation on the glycemic profile, inflammatory markers, and oxidative stress in HIV‐infected individuals under antiretroviral therapy. This double‐blind, crossover, randomized clinical trial was composed of 20 subjects arranged initially into experimental group (n = 10) and placebo group (n = 10) groups, receiving 1,000 mg curcumin/day or microcrystalline cellulose/day, respectively, during a 30‐day period and 12‐day washout. Subsequently, the groups were switched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They demonstrated that curcumin supplementation did not considerably improve the glycemic profile, inflammatory indices, and oxidative stress level of HIV-infected patients. 26 Among the nutritional variables which were assessed in the current trial, serum albumin, pre-albumin, and transferrin levels did not change significantly between the study groups. However, total lymphocyte count showed a significant increase in the NC group compared to the placebo group.…”
Section: Papermentioning
confidence: 63%
See 4 more Smart Citations
“…They demonstrated that curcumin supplementation did not considerably improve the glycemic profile, inflammatory indices, and oxidative stress level of HIV-infected patients. 26 Among the nutritional variables which were assessed in the current trial, serum albumin, pre-albumin, and transferrin levels did not change significantly between the study groups. However, total lymphocyte count showed a significant increase in the NC group compared to the placebo group.…”
Section: Papermentioning
confidence: 63%
“…In addition, the APACHE II and NUTRIC scores were notably improved in patients with traumatic brain injury after treatment with curcuminoids. 39 Furthermore, in contrast to earlier studies, Silva et al , 26 in a double-blind, crossover, randomized clinical trial study, examined the impacts of curcumin administration (1000 mg day −1 for 1 month) on the glycemic profile, inflammatory indices, and oxidative stress level in HIV-infected patients receiving antiretroviral treatments. They demonstrated that curcumin supplementation did not considerably improve the glycemic profile, inflammatory indices, and oxidative stress level of HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations